The nursing team work process in Children and Adolescents Psychosocial Care Centers - Delfini, Giulia; Toledo, Vanessa Pellegrino; Garcia, Ana Paula Rigon Francischetti (Revista da Escola de Enfermagem da USP, 2021)
Objective: To know the nursing team work process in Children and Adolescents Psychosocial Care Centers in a city of the state of São Paulo. Method: This is a qualitative, descriptive, and exploratory study, based on the approach of historical and dialectical materialism, carried out with the nursing team through participant observation and semi-structured interviews. Results: Eleven subjects from the nursing team participated in the study. The nursing team work process emerges from the dialectical tension of two categories: the non-knowledge, based on the alienation of the nursing work process and subordination to the knowledge of the multidisciplinary team, and the knowledge based on the nursing clinic outlined within the biological and relational perspectives. Conclusion: The nursing team work process takes place when guided by a non-knowledge resulting from alienation due to the knowledge of the other, and by knowledge through the implementation of the Nursing Process through the Nursing Care Systematization based on a biological perspective, considering relational and administrative aspects, which emerges as a contradiction.